Decision Support System for Distribution of Assistance for Fishermen with Analytical Hierarchy Process - Prind Triajeng Pungkasanti (Politeknik Negeri Semarang, 2019)
Sei Kapitan (Kapitan River) is a village located in Kumai District, West Kotawaringin Regency, Central Kalimantan Province with a population density of 5,660 inhabitants. 25% from 5,660 people work as fishermen so do fishermen in this village). The government has provided assistance for fishermen to reduce poverty, but it isn’t in the right target. The government only provides assistance without providing standard data and criteria to determine the beneficiaries. While from the village, they chose beneficiaries based on meetings with village officials, there will be many factors recommended at the meeting. Therefore they need system that can determine and conduct the assistance to fishermen who are entitled to receive support, it is the AHP (Analytical Hierarchy Process) method. By using the system development method, called prototypes, and criteria for fisheries ownership every month, types of fisheries, ship, and fishing gear ownership can be detected. This method was chosen because it can select the best alternative from several alternatives. The final result of this system is an alternative decision making that is interesting in determining the beneficiary fishermen. The future hope is that the results of decision making will be right on target and the system can be operated online.